18F-Fluciclovine PET/CT Detection of Recurrent Prostate Carcinoma in Patients With Serum PSA ⩽ 1 ng/mL After Definitive Primary Treatment. (March 2019) - England, Joseph R.; Paluch, Jeremy; Ballas, Leslie K.; Jadvar, Hossein
Abstract : Purpose: The aims of this study were to report on our initial experience using 18 F-fluciclovine PET/CT to detect recurrent prostate carcinoma in patients with low serum prostate-specific antigen (PSA) after definitive treatment of primary disease and to conduct a preliminary investigation for factors associated with positive scan findings. Patients and Methods: In this retrospective study, 18 F-fluciclovine PET/CT scans from 28 men with suspected recurrence of prostate carcinoma and PSA values of 1 ng/mL or less were examined to identify the site(s) of disease recurrence. Differences in detection rate for Gleason scores of 7 and greater than 7, T2 and T3 disease, negative and positive surgical margins, and negative and positive seminal vesicle invasion were compared using the Fisher exact test. Mean PSA and mean PSA doubling time of patients with positive scans and negative scans were compared using the independent 2-group t test. Results: At least one site of disease recurrence was identified in 13 (46.4%) of 28 patients. Disease detection rate was significantly higher in patients with history of Gleason score greater than 7 (Fisher exact test, P = 0.004). Mean PSA and PSA doubling time were not significantly different between patients with positive and negative 18 F-fluciclovine PET/CT scans ( P = 0.29 and 0.70, respectively). Conclusions: Detection of recurrent prostate cancer using 18 F-fluciclovine PET/CT is possible in patients with low but rising PSA levels of 1 ng/mL or less. In such patients, local and nodal recurrences are more common than distant metastasis, and Gleason score greater than 7 is associated with positive scan results.